Requirement Politics: Poetry as Feminist Response to Institutional Reluctance and Dismissal - Bowen, Bernadette (Art/Research International)

(untitled) (University of Alberta, 2023)
In this article, which includes a feminist micro-chapbook, the author has chosen poems written both prior to and following their recollection of and subsequent therapeutic struggle to work through their lifelong experiences of sexual harassment and assault. Situated within the neoliberally co-opted #MeToo campaign, Betsy Devos’s 2020 Title IX cross-examination mandate, and post-Trumpian, ongoing COVID U.S. landscape, this work performs an ethnographic autopsy on the body politic: displaying the fleshy lived consequences of an unjust legal system. By continuing Faulkner’s work on poetic inquiry as feminist methodology, this piece contributes to the tradition of poetic praxis as a means of clapping back to structures of oppression. At its core, this article reveals relived experiences and words spoken by institutional figures reluctant to fulfill mandatory reporting requirements. By playing off Higginbotham’s (1993) term respectability politics, “Requirement Politics” blurs lines of academic and poetic writing to deliberately collapse a fabricated line between public and private lived experiences.